2014
DOI: 10.14687/ijhs.v11i1.2165
|View full text |Cite
|
Sign up to set email alerts
|

Bireyleri rekreasyonel egzersize güdüleyen faktörlerin belirlenmesi: Demografik farklılıklar

Abstract: The purpose of this study was to investigate and compare the motivational factors that motivate individuals to the recreational exercise participation with regard to demographic variables. 302 male (55,1%) and 246 female (44,9%) with a total of 548 recreational exercise participants from 9 health and fitness centers, in Ankara, participated voluntarily to this study. "Recreational Exercise Motivation Measure" was used as means of data collection instrument. Independent Samples t-test was used to examine the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
0
4
0
4
Order By: Relevance
“…It is determined that women who do regular exercise mostly do so to be healthy (34.8%), and to look beautiful and strong (13.3%) (Polat, 2014). In another study, it is stated that in the health sub-dimension, female participants had higher scores than male participants (Güngörmüş et al, 2014). Similarly, according to Çağlar et al (2009), it was observed that in the health sub-dimension, women's scores were higher than those of men.…”
Section: Discussionmentioning
confidence: 88%
“…It is determined that women who do regular exercise mostly do so to be healthy (34.8%), and to look beautiful and strong (13.3%) (Polat, 2014). In another study, it is stated that in the health sub-dimension, female participants had higher scores than male participants (Güngörmüş et al, 2014). Similarly, according to Çağlar et al (2009), it was observed that in the health sub-dimension, women's scores were higher than those of men.…”
Section: Discussionmentioning
confidence: 88%
“…Çünkü insanlar davranışlarının sonuçlarını değerlendirdiklerinde, olumlu sonuçlar beklerlerse olumlu tutumların davranışsal niyeti artıracağı varsayılmaktadır (22). Benzer şekilde, boş zaman etkinliklerine katılımın arkadaşların katılımı nedeniyle (% 60) gerçekleştiği saptanmıştır (25). Bu açıdan bakıldığında, tıpkı planlı davranış teorisinin iddia ettiği gibi, insanların başkalarının davranışlarını gözlemleyip olumlu tutumlar geliştirdikçe davranışı gösterme olasılıkları artmaktadır.…”
Section: Tutum Bileşeniunclassified
“…Çünkü insanlar sonuçları düşünürler ve daha sonra bu beklenen sonuçlarla kendilerini motive ederler. Bu çalışmada da sağlık, beceri geliştirme ve fiziksel görünüm beklenen sonuçlar olarak belirlenmiş ve bu beklenen sonuçlar kişilerin davranışsal niyetini artıran olumlu tutumlar geliştirmelerine yardımcı olduğu belirlenmiştir (25). Ayrıca, davranış değişikliğinin yararları ve zararları hakkında bilgi vermek, egzersiz davranışlarının olumlu yönde değiştirilmesine yönelik kararlarda etkilidir.…”
Section: Planlı Davranış Teorisi Ve Sportif Davranışlarunclassified
“…Güngörmüş vd. çalışmasında (Güngörmüş, Yenel, & Gürbüz, 2014) katılımcıları rekreasyonel egzersize güdüleyen faktörlerin sağlık, beceri gelişimi,vücut ve dış görünüm, sosyal ve eğlence ve rekabet olduğunu tespit etmiştir. Buna ek olarak, bireyleri rekreasyonel amaçlı egzersize güdülenmelerinde en çok etkiye sahip olan faktörün "sağlık", en az etkiye sahip olan faktörün ise "rekabet" olduğunu da savunmuştur.…”
Section: Kavramsal çErçeve 21 Rekreasyon Kavramıunclassified